Given the sequence:
23, 16, 9, 2
Use the arithmetic sequence formula:
![a_n=a_1+(n-1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/8ad7drcg9vuq9sminhqfaw7j3r5r4u1ij9.png)
Where
an = nth term
a1 = first term
n = number of terms
d = common difference
d = a2 - a1 = 16-23 = -7
Since d = -7, let's find the equation for the nth term.
![\begin{gathered} a_n=23+(n-1)-7 \\ a_n=23+n(-7)-1(-7) \\ a_n=23-7n+7 \\ \text{Combine like terms} \\ a_n=-7n\text{ +23}+7 \\ \\ a_n=-7n+30 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r2vsacxeavvcgea1b74q111i6ua12u0veu.png)
The equation for the nth term is:
![a_n=-7n+30](https://img.qammunity.org/2023/formulas/mathematics/college/nm4sqqk1jmwp2k4ky2d89s3jmlb39mfrfu.png)
Let's find the 25th term, a25:
Substitute n for 25 and evaluate
![\begin{gathered} a_(25)=-7(25)+20 \\ \\ a_(25)=-175+30 \\ \\ a_(25)=-145 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tnkxu2mgy1uhxshv6smm9qjfa154s9gi3l.png)
ANSWER:
![\begin{gathered} a_n=-7n+30 \\ \\ \\ a_(25)=-145 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3a4k005unpnyihrkdvagju137griphgyjp.png)